Blood hormones and suicidal behaviour: A systematic review and meta-analysis. (August 2022) - Fu, Xue-Lei; Li, Xia; Ji, Jia-Mei; Wu, Hua; Chen, Hong-Lin
Abstract: This study was to evaluate the relationship between blood hormone levels and suicidal behaviour. We reviewed Web of Science, PubMed and Embase for literature published up to 10 April 2022. Studies were restricted to English-language articles. Studies measuring blood hormone levels in suicidal and non-suicidal subjects were eligible. Standardized mean differences (SMDs) were applied to evaluate group differences. Overall, 57 studies were eligible, of which 51 evaluated suicide attempts, and 9 assessed suicidal ideation. Random-effects meta-analysis indicated that levels of thyrotropin stimulating hormone (TSH) (SMD = 0.50; 95% CI, 0.27–0.72), leptin (SMD = −1.16; 95% CI, −1.94 to −0.38) and dehydroepiandrosterone sulfate (DHEAS) (SMD = −0.67; 95% CI, −1.13 to −0.21) were related to suicide attempts, whereas progesterone levels (SMD = 0.22; 95% CI, 0.03–0.41) were related to suicidal ideation. This analysis offers evidence linking abnormalities of blood hormones with suicidal behaviour, which may be essential for identifying individuals with suicide attempts and suicidal ideation. Large prospective studies are needed for further clarification of roles of hormones in suicidal behaviour. Highlights: TSH, leptin and DHEAS levels were associated with suicide attempts. Progesterone levels were associated with suicidal ideation. Assessment of suicide risk in conjunction with hormone levels may be essential.